การวิเคราะห์หาปัจจัยเสี่ยงและการติดตามความเสี่ยงต่อการหกล้มในช่วงเวลากลางคืนของผู้สูงอายุโดยใช้ผู้ป่วยพาร์กินสันเป็นต้นแบบในการศึกษา - รุ่งโรจน์ พิทยศิริ (คณะแพทยศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2016)
Physiologic studies of nocturnal movement: Unlocking the secrets of nighttime falls in the elderly by using Parkinson s disease as a study modeL Purpose: To develop a portable ambulatory motion recorder (the NIGHT-Recorder) that can quantify nocturnal hypokinesia in patients with Parkinson s disease (PD). Method: The NIGHT-Recorder consists of five modules: a microcontroller, a power management module, a sensor module, a real-time clock module, and a data storage module. The sensor module includes 16-bit digital-output triaxial integrated microelectromechanical system accelerometers that were specifically designed to measure intensity of movements and to register position of the human body with respect to gravity, providing information on rotations in the longitudinal axis while lying in bed. The signal processing utilizes the forward derivative method to identify turning over and getting out of bed as primary indicators. The prototype was tested on 6 PD pairs (6 PD patients and their spouses) to verify and measure their nocturnal movements for one night. Results: Using pre-determined definitions, 134 discrete movements were captured in one night consisting of rolling over 115 times and getting out of bed 19 times. PD patients rolled over Significantly fewer times than their spouses (p=0.028), and the extent of position change was Significantly smaller in PD patients (p=0.028). The duration of the new position achieved following rolling over was not significantly different between the two groups. However, PD patients rolled over at a significantly slower speed (p=0.028) and with slower acceleration (p=0.028) than their spouses. In contrast, PD patients got out of bed Significantly more often than did their spouses (p=0.02). Conclusion: It is technically feasible to develop an easy-to-use, portable, accurate, and cost effective device (approx. $8OO) that can assist physicians in the assessment of nocturnal movements of PD patients. Additional studies are needed to develop protocols to assess the full spectrum of nocturnal akinesia in a larger number of PD patients.